Frequently Asked Questions about Landscape Fertilization for Florida-Friendly Landscaping Ordinances - Jerry B. Sartain; Laurie E. Trenholm; Edward F. Gilman; Thomas A. Obreza; Gurpal Toor (EDIS)
Revised! ENH-1115, a 10-page fact sheet by J.B. Sartain, L.E. Trenholm, E.F. Gilman, T.A. Obreza, and G. Toor, was created to help guide local government officials in developing local regulations based on science. It uses a question-and-answer format to address common concerns related to fertilizers, best management practices (BMPs), landscapes and their maintenance. Includes references. Published by the UF Department of Environmental Horticulture, January 2009.